Phytochemical analysis of Cynara scolymus L. cultivated in Mongolia - Tsevegsuren, N; Davaakhuu, G; Udval, Ts (Mongolian Journal of Chemistry, 2014)
Cynara scolymus L. (Artichoke) is a traditionally consumed vegetable in many countries. In Mongolia, this plant has been successfully cultivated during the last years. The present study is an attempt to investigate the phytochemical composition of C.scolymus L. The result reveals the presence of bioactive constituents comprising flavonoids, total phenolic compounds, saponins and total proteins, carbohydrates, lipids and vitamin C in plant parts. The presence of these phytochemicals can be correlated with the medicinal potential of this plant. DOI: http://doi.dx.org/10.5564/mjc.v15i0.320 Mongolian Journal of Chemistry 15 (41), 2014, p40-42